1999
DOI: 10.1016/s0022-5347(05)68241-9
|View full text |Cite
|
Sign up to set email alerts
|

Transdifferentiation of Prostate Cancer Cells to a Neuroendocrine Cell Phenotype in Vitro and in Vivo

Abstract: Exposure of LNCaP cells to a hormone deficient medium drastically increased cyclic AMP production and this may identify the biochemical pathway through which hormone depletion induces a neuroendocrine conversion of prostate cancer cells. Hormone depletion also reduced TGF-beta2 mRNA expression and this finding was consistent with our inability to demonstrate any effect of TGF-beta2 on neuroendocrine conversion in vitro. Finally, our demonstration of increased neuroendocrine cells found in LNCaP tumors growing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

12
94
0
1

Year Published

2002
2002
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 152 publications
(107 citation statements)
references
References 23 publications
12
94
0
1
Order By: Relevance
“…This finding supports the trans-differentiation model and suggests that NE cells may be derived from the non-NE secretory-type cancer cells (13,14). However, the signaling pathway involved in the differentiation process is unclear.…”
Section: Prostate Cancer (Pc)supporting
confidence: 78%
See 2 more Smart Citations
“…This finding supports the trans-differentiation model and suggests that NE cells may be derived from the non-NE secretory-type cancer cells (13,14). However, the signaling pathway involved in the differentiation process is unclear.…”
Section: Prostate Cancer (Pc)supporting
confidence: 78%
“…Androgen withdrawal of the culture media leads to NED of LNCaP cells, a PC cell line (13), mimicking in vivo observation in PC patients treated hormonally. This finding supports the trans-differentiation model and suggests that NE cells may be derived from the non-NE secretory-type cancer cells (13,14).…”
Section: Prostate Cancer (Pc)mentioning
confidence: 68%
See 1 more Smart Citation
“…This implies that neuroendocrine differentiation probably occurs through distinct intracellular pathways, as previously hypothesized (11), even if there are few evidences that depletion in androgens can increase intracellular cAMP (32) in prostate LNCaP cells. In addition, androgen removal increased the proportion of cells expressing the T-type calcium current and the overall calcium current density.…”
Section: Discussionmentioning
confidence: 51%
“…Burchardt et al reported that LNCaP cells inoculated into castrated mice induced a significant increase in NE cells compared with those in intact mice. 28 Although the mechanism of NE transdifferentiation induced by androgen deprivation of AR-dependent PCa cells has been investigated, the mechanism mediating NE differentiation is still not clear. 29 Our data demonstrated that fibroblasts stimulated proliferation and AR expression in PCa cells under androgen deprivation in vitro.…”
Section: Discussionmentioning
confidence: 99%